MINORITY RIGHTS IN ISLAM: ETHICAL FOUNDATIONS, PROPHETIC PRACTICE, AND JURISTIC REINTERPRETATION (Al-Aasar, 2025)
This article examines minority rights in Islam through the analysis of the Qur’ānic principles, Prophetic practice, and contemporary juristic discourse. It argues that the protection of religious minorities is not a marginal concern but a core ethical obligation. Discussions on Islam and pluralism evaluate the tradition through the lens of minority rights, relying on selective historical practices or politicized interpretations of the past. Such approaches risk confusing the normative ethical foundations rooted within Islamic revelation and jurisprudence. This study employs a qualitative, normative-analytical methodology and it engages classical Qur’ānic exegesis, Prophetic practices, and modern maqāṣid-based interpretations to explore how Islamic law conceptualizes justice, human dignity, and religious freedom in plural societies. The analysis determines that while classical juridical frameworks such as the dhimma system were shaped by pre-modern political contexts, their underlying ethical objectives—justice, security, and social harmony remain normatively binding. Modern juristic discourse prioritizes these objectives in articulating models of citizenship and legal equality suited to present nation-states. By combining foundational texts with evolving juristic reasoning, this study contributes to Islamic legal and ethical scholarship by offering a principled framework for minority rights based on Islamic moral philosophy rather than historical legal forms.